حرية المرأة بين نصوص الوحي والمنظمات النسوية في بنغلاديش: دراسة تحليلية تقويمية = Freedom of women: a critical comparison between the women’s organisations in Bangladesh and the Islamic scripture - Ali, Md Rahmat; Amanullah, Muhammad (IIUM Press, International Islamic University Malaysia, 2020)
This article discusses viewpoints of several women's organizations in Bangladesh pertaining to the issue of the freedom of women. The central issues of the study relate to the concepts of women’s freedom. Following the inductive, analytical and comparative methods, the two researchers discusses these concepts in light of what is available in Islamic scripture and what is maintained and demanded by women’s organizations in Bangladesh. Then they conduct a comparative study between the two sources. The result of the study reveals fundamental differences between the commandments of Islamic scripture and the stance of feminist organizations of Bangladesh regarding the concepts of woman’s rights and her equality with man. The study also explains the necessity of an appropriate understanding of the term “woman’s rights”. This research finds that both Islamic scripture and women’s organizations in Bangladesh have given emphasise on providing women their freedom.